Decoding the Cognitive Footprint of Autism: Unveiling the Nexus between Autism Spectrum Disorder and Cognitive Abilities in Children with Special Needs - Windarwati, Heni Dwi; Lestari, Retno; Hidayah, Ridhoyanti; Hasan, Haliza; Kusumawati, Mira Wahyu; Ati, Niken Asih Laras; Selena, Irhamna Nias; Dumar, Bergita; Rahayu, Gemi; Maharani, Asri (Sawwa: Jurnal Studi Gender, 2024)
Children with special needs experience disruptions in their physical, mental, and cognitive development and socialization, causing their daily activities to differ from other children. One classification of children with special needs was Autism Spectrum Disorder (ASD), in which the status and severity of ASD symptoms are related to cognitive abilities. This study aimed to determine the relationship between autism status in children with special needs and their cognitive abilities. This study employs a quantitative design with a cross-sectional method and involves 55 children with special needs in Malang City, East Java Province, Indonesia. The study was conducted on 55 children with special needs in Malang City in East Java Province, Indonesia. The Autism Spectrum Quotient (AQ-10) questionnaire was used to measure autism status, and cognitive abilities were measured using the Autism Treatment Evaluation Checklist (ATEC). This study showed that as many as 85.5% of children with special needs have characteristics that lead to autism. Most children lived with siblings (72.8%), and 21.8% had siblings with the same condition. The Spearman-Rho analysis indicated a significant relationship between autism status and cognitive abilities (coefficient: 0.425; p-value=0.001). Our study found that children with special needs tend to have ASD status, so children with ASD need to get cognitive therapy according to their abilities. Therefore, parents and special needs schools must collaborate to enhance the cognitive abilities, quality of life, and overall health of special needs students through therapy focused on child's abilities to help them achieve independence and productivity.